La violence par partenaire intime : enjeux traductologiques et politiques des catégorisations de la violence - Samantha Saïdi (Glad!)
This article proposes a social and political translation study that focuses on the circulation and methods of circulation (translation, re-use, re-analysis, ...) of the categories of violence adopted by the multidisciplinary field studying intimate partner violence (IPV). Questioning gender prejudices conveyed in French translations or re-uses of categorizations produced by two American feminist sociologists, Johnson (2006) and Renzetti (1992), the article proposes a linguistic and semantic explanation. This study confirms that their translations or reuses carry traces of gender prejudices that we can often attribute to those who translate if not to the authors. Thus, the terms lesbian violence, intimate partner violence or symmetry of violence used in the translations or reuses of these texts are not neutral but convey the idea of a masculine or lesbian essentialization of violence, or of a vertical or horizontal complementarity between men and women in violence, which is denounced by the feminist perspectives used by Johnson and Renzetti.